Utilization of Maternal Health Services among Married Women of Reproductive Age (MWARA) at Selected Rural Municipality in Nepal: A Cross-sectional Study - Kapar, Vijay Kumar; Giri, Mahendra; Chhantyal, Chundevi; Giri, Shree Shyam; Godar, Suruchi; Shah, Poonam (NPRC Journal of Multidisciplinary Research, 2025)
Background: Maternal health refers to the health of women during pregnancy, delivery, and the postpartum period, and the services include promotive, preventive, therapeutic, and rehabilitative health services for mothers and children provided by health facilities. Maternal and child health services are a priority program for community health. The main objective of this study was to assess the utilization of maternal health services among married women of reproductive age (MWARA). Methods: A quantitative descriptive cross-sectional study design was adopted to assess the utilization of maternal health services. The 157 MWARA aged between 19 and 45 years were employed for this study from June to July 2024 at Tamankhola Rural Municipality, Baglung District, Gandaki Province, Nepal. The study employed a simple random sampling technique to select the wards, and a purposive sampling technique was used to get respondents. A face-to-face interview with a semi-structured questionnaire among MWARS who had at least one child under two years was applied. The data were gathered, and univariate analysis was done by using IBM SPSS version 27 to disseminate the study’s findings. Results: Out of 157 respondents, nearly half (42.8%) belonged in nuclear families, while a little bit more than half (58.59%) belonged in joint families. Most respondents (63.69%) married before the age of 20, and similarly (61.15%) had their first pregnancy at this young age. The majority of women (91.72%) had visited a health facility by walking on their feet. The utilization of antenatal care (ANC) services at least four or more times was found to be 97.45%, where a significant number (2.55%) of women didn’t utilize recommended ANC services as per protocol. Likewise, 66.88% were counseled on delivery preparation, 76.43% on breastfeeding, and 61.15% on recognizing pregnancy danger signs. Similarly, all the women (100%) received the Tetanus Diphtheria (TD) vaccine, and all mothers gave birth in a healthcare facility and found that all the mothers received recommended postnatal care (PNC), viz. most of them (96.2%) had three PNC visits, while few of them (3.8%) received only two PNC services. Conclusion and Recommendation: The study found that most women utilized ANC, delivery and neonatal care, and PNC services, with fully institutional delivery, and there were no home deliveries, which led to low pregnancy complications and mostly normal deliveries. All women received PNC services, and most of the newborns were bathed after an hour of birth. Likewise, a significant number of women received vitamin A and IFA supplements after delivery. The investigators recommended that the policymaker reform the policy that incorporates the provision of maternal health services planning, implementation, and evaluation primarily by the local government with data-driven decision-making practice since maternal health is a concurrent responsibility of three tiers of government.